Mushroom foraging & feasting : recollections and recipes from a lifetime on the hunt - Romanoff, Victoria (Abbeville Press Publishers, 2022)
Romanoff introduces readers to twelve of the most easily foraged and delicious mushrooms, including the chanterelle, the morel, and the oyster. She describes the appearance, habits, and lore of each variety, and provides a recipe for each; her recipes include both refined kitchen creations and rustic dishes meant to be prepared over an open fire at the end of a successful hunt. Romanoff also shares personal stories from her eight decades of mushrooming. From serendipitous discoveries while canoeing to habitual hikes with Piglet (in fact a terrier, not a truffle pig), her detailed accounts bring alive the sensory experience of the hunt, and the particular connection with nature that a forager enjoys.